Process Modelling Sistem Informasi Penjualan Dan Pembelian Obat Pada Apotek Rindani Sejahtera Pekanbaru - Akhmad Zulkifli, Welpendi Dalimunthe. (RJOCS (Riau Journal of Computer Science), 2018)
Process Modeling approach to Analysis and design of information systems at the drug sale Rindani sejahtera pharmaci Pekanbaru Core Solutions aims to create a computerized system that can be used by the company in running the company's operations, where they are always in need of information. The methodology used in this research is the methods of literature, include drug and literature, as well as conduct research by holding recording, collecting and analyzing reports, interviews to the company, and the methods of analysis and design of information systems sales approach. Results obtained from this study is a need for sales information systems, such as sales reports that can help management in decision making. So therefore, the right decision and the quality will be produced, which in turn will be able to increase drug sales.